1941
DOI: 10.1085/jgp.24.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Measurement of Visual Mechanisms

Abstract: IOn comparing monocular and binocular critical points for visual flicker, within the fovea, it was found by Sherrington (1902, 1904, 1906) that for similar phases of interrupted illumination fa]Hng synchronously on each retina there was very little reinforcement, so that the binocular fusion frequency was almost the same as when using one eye (or a little higher). The observations were made at a comparatively high flash intensity, and thus at a high flash frequency, save for some incidental tests. No mention w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1959
1959
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Using white-light flashes and varying flash duration across a range from 10% to 90%, i . e ., from 100 ms to 900 ms per one-second interval, Crozier & Wolf [ 12 ] found the flash intensity required to produce fusion was increased as the percentage of light in the duty cycle was increased. This means that persistence of flash influence is longer with shorter-duration flashes.…”
Section: Resultsmentioning
confidence: 99%
“…Using white-light flashes and varying flash duration across a range from 10% to 90%, i . e ., from 100 ms to 900 ms per one-second interval, Crozier & Wolf [ 12 ] found the flash intensity required to produce fusion was increased as the percentage of light in the duty cycle was increased. This means that persistence of flash influence is longer with shorter-duration flashes.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of the temporal resolution of vision come from a variety of different tasks but can be divided into two groups of temporal limits: a fast group that operates on the order of 10s of milliseconds and a slower group of visual mechanisms taking more than 100 ms ( Holcombe, 2009 ). The fast temporal limits are usually explained by temporal integration of low-level visual features (like in the case of flicker fusion or integration masking; Crozier and Wolf, 1941 ; Kietzman and Sutton, 1968 ; Scheerer, 1973a , b ; Di Lollo and Wilson, 1978 ; Coltheart, 1980 ; Enns and Di Lollo, 2000 ; Breitmeyer and Öğmen, 2006 ). In contrast, slower temporal limits are usually associated with high-level processing in an object-based frame of reference like in the case of feature conjunctions across space (color-shape: Holcombe and Cavanagh, 2001 ; or orientation-location: Motoyoshi and Nishida, 2001 ) or consolidation of objects in visual working memory ( Gegenfurtner and Sperling, 1993 ; Vogel et al, 2006 ).…”
Section: Temporal Resolution Of Visuo-spatial Object Processingmentioning
confidence: 99%
“…From this he concluded that Talbot-Plateau integration was accomplished at the level of the retina. Crozier and Wolf (1941) re-evaluated the issue and supported Sherrington’s position. Shevell et al (1992) have taken the opposite view, providing evidence for a cortical basis for contrast and assimilation of brightness using dichoptic stimulation.…”
Section: Discussionmentioning
confidence: 92%